2019
DOI: 10.1021/acs.nanolett.9b00338
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Chemical Interface Damping: Interfacial Electronic Effects of Adsorbate Molecules and Sharp Tips of Single Gold Bipyramids

Abstract: The optimization of the localized surface plasmon resonance (LSPR)-decaying channels of hotelectrons is essential for efficient optical and photochemical processes. Understanding and having the ability to control chemical interface damping (CID) channel contributions will bring about new possibilities for tuning the efficiency of plasmonic hot-electron energy transfer in artificial devices. In this scanning electron microscopy-correlated dark-field scattering study, the CID was controlled by focusing on the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
137
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(150 citation statements)
references
References 39 publications
7
137
1
2
Order By: Relevance
“…Actually, it has been reported that the CID pathway is well tunable by different types of ligands. [ 36 ] To this end, we exchange four types of thiol ligands with similar molecular structures but different substituents on a benzene ring onto the surface of RS‐Au nanocrystals, including 4‐MP with a para OH group, 4‐nitrothiophenol (4‐NTP) with a para NO 2 group, 4‐mercaptobenzoic acid (4‐MBA) with a para COOH group, and 4‐aminothiophenol (4‐ATP) with a para NH 2 group. As shown in Figure S18 in the Supporting Information, the extinction spectra of surface exchanged RS‐Au colloidal solution exhibit different degrees of plasmon peak broadening and red‐shift, which are characterized for the CID effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, it has been reported that the CID pathway is well tunable by different types of ligands. [ 36 ] To this end, we exchange four types of thiol ligands with similar molecular structures but different substituents on a benzene ring onto the surface of RS‐Au nanocrystals, including 4‐MP with a para OH group, 4‐nitrothiophenol (4‐NTP) with a para NO 2 group, 4‐mercaptobenzoic acid (4‐MBA) with a para COOH group, and 4‐aminothiophenol (4‐ATP) with a para NH 2 group. As shown in Figure S18 in the Supporting Information, the extinction spectra of surface exchanged RS‐Au colloidal solution exhibit different degrees of plasmon peak broadening and red‐shift, which are characterized for the CID effects.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding order in CID enhancement coincides well with the literature. [ 36 ] Interestingly, RS‐Au nanocrystals exchanged with these four types of thiol ligands exhibit quite different activity toward the H 2 production, which clearly indicates that ligands play a key role in the hydrolysis of AB molecules. Moreover, the activity exactly follows the order of CID enhancement as 4‐NTP > 4‐MBA > 4‐MP > 4‐ATP, which unambiguously demonstrates that the direct electron transfer mediated by CID pathway dominates the reaction activity.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, experimental evidence shows that CID by adsorbates is able to retard the thermalization process of hot charge carriers (picosecond regime) by the repeated back and forth transfer of hot electrons between the metal and the adsorbates [165] . Some factors need to be taken into account in order to increase efficiency by CID [166] . In contrast to the indirect transfer mechanism, the direct electron transfer requires not only an orbital overlap, but also strong hybridization between the metallic nanoparticle surface and the adsorbate [152] .…”
Section: Optoelectronic Effects In Coupled Organic–inorganic Nanostrumentioning
confidence: 99%
“…Darüber hinaus zeigen experimentelle Belege, dass die CID durch Adsorbate in der Lage ist, die Thermalisierung der heißen Ladungsträger (Picosekundenbereich)zu verzögern, indem die heißen Elektronen wiederholt zwischen Metall und Adsorbaten hin und her übertragen werden [165] . Um die Effizienz durch CID zu steigern, müssen einige Faktoren berücksichtigt werden [166] . Im Gegensatz zum indirekten Transfermechanismus erfordert der direkte Elektronentransfer nicht nur eine Orbitalüberlappung, sondern auch eine starke Hybridisierung zwischen der Oberfläche der metallischen Nanopartikel und dem Adsorbat [152] .…”
Section: Optoelektronische Effekte In Gekoppelten Organisch‐anorganisunclassified